Biliary complications: the Achilles’ heel of ALPPS - Muthukrishnan, Srinivasan; Amudhan, Anbalagan; Rajendran, Shanmugasundaram (International Surgery Journal, 2018)
ALPPS (associated liver partition and portal vein ligation for staged hepatectomy) is a novel procedure enabling rapid hypertrophy of the future liver remnant (FLR) in less than a week. However, it is associated with a high morbidity of 33 - 64% mostly biliary. We report a 37-year-old female with sigmoid colon cancer and synchronous liver metastasis occupying the right liver including segment 4 managed by colonic resection with ALPPS enabling an extended right hepatectomy. Postoperatively the patient had a gradual rise in bilirubin and MRCP revealed biliary stricture which was managed by PTBD followed by internalization. Biliary complications seem to be a major determinant of perioperative outcomes and success of ALPPS. Important preventive measures include accurate preoperative imaging, careful dissection of porta, use of vessel loops and transcystic stents during ALPPS-1. Treatment of biliary complications mainly centres around appropriate use of endoscopic and interventional radiological procedures.